Personal value and leadership effectiveness - Al Halbusi, H. (UMRR, 2016)
Researchers investigating the links between value and leadership influences suggest that the behavioral characteristics that differentiate one leadership paradigm from another may be explained through assessing differences in the leader’s value and belief systems.